Estabilidade de agregados dos solos de uma topolitossequência da bacia hidrográfica do Ribeirão àgua Iguaraçu, Iguaraçu - PR - Villa, João Fernando Dalla (2016)
This study was developed in Iguaraçu PR, specifically in the basin waters Igaraçu, located in the north of Paraná state. The research was conducted in a slope where soils from different origins are identified like high slope soil are found derived from Caiuás formation and in low slope soil are derived from the Serra Gerals formation. On the above, this study aimed to evaluate the aggregate stability of soil volumes and the factors responsible by aggregation such as organic matter, organic carbon, natural clay, flocculation of the clays and the fractions in a slope that is submitted to the use of same management process. To achieve the objectives of this study was used the study method of structural analysis of soils cover. This method enables monitor soil volumes of behavior in time and space and the results can be represented in future cartographic products. The results showed that the volumes of soils derived from Caiuá training are volumes with little clay and low flocculation and unstable, with little organic matter, but which interferes with the stability of aggregates, with volumes that have a higher percentage of organic matter also showed larger aggregates. And in general, the volumes coming from Caiuá training had the majority of households in classes of 0.59 and 0,250mm. However, Bt and Bw1 volumes of the TR-2 despite belonging the same line, had the majority of households in classes 2 and 1 mm, this result may be related to the clay since both volumes have higher amount of this fraction. When compared to the volumes belonging to Caiuá training. The volumes of soils derived from the Serra Geral formation, these very clay, which is well flocculated and little expense, showed the majority of households in classes 2 and 1 mm, and these volumes between the parameters analyzed, the clay was one of the main factors that interfered with aggregate stabilityresults. The profile of topolithosequence facilitates observe where it occurs transitions of geological formations and the lateral and vertical contact volumes of soil, making it possible to understand the behavior of volumes along the slope